The 2021 Madrilenian regional election: how can the incumbent improve its results in times of crisis? - Coulbois, Jaime (Frontiers in Political Science, 2023)
Introduction Although there is a considerable amount of work on the effect of catastrophes on elections, we still do not have much work on the impact of the COVID-19 pandemic on them. This article focuses on the case of the Madrilenian regional election of 2021, looking for the causes of the improvement of the ruling party's results, the Popular Party (PP), which went from having 22.23% of the vote share in 2019 to 44.76% in 2021, and more concretely to the role that COVID-19 had on this. This election is especially interesting for this matter because the main issue was the question of how to manage the pandemic: The right-wing parties (and mainly the PP) criticized the restrictions imposed by the central government, led by the socialist Pedro Sánchez, while the left-wing parties defended them. Methods The article runs separate analyses at the aggregate and individual levels. At the aggregate level, it uses municipal and district-level data with electoral and socio-demographic variables; at the individual level, it uses a post-electoral survey. Results There was a higher improvement in PP's results in areas with higher increase in the turnout rate, and both individual and aggregate-level data show that this improvement was also led by upper-class and young voters. However, there is no significant association with the cumulated cases of COVID-19 in the area. Discussion The article contributes to the understanding of the 2021 Madrilenian regional election, showing that, despite the politicization of the pandemic, there was no relationship between how hardly were the areas hit by the pandemic and the outcome of the election at the aggregated-level.